Implementing a public health approach to the management of chronic pain in the USA. (July 2013) - Gupta, Anita; Weber, Nicholas; Duwell, Monique
SUMMARY Chronic pain represents a staggering public health burden. Despite research and technologic advances in pain management, chronic pain is grossly undertreated in the USA. Many pain patients are dissatisfied with their treatment regimens, and disparities exist in pain treatment for minorities and for socioeconomically disadvantaged and elderly patients. Many doctors feel inadequately trained to treat chronic pain. Therapeutic opioid use for chronic pain is a particularly challenging issue for both physicians and patients. Strategies for addressing chronic pain from a public health perspective include increased education of physicians and the public, improved integration of pain management across disciplines, and improved systems for monitoring prescription opioids.